Novel loci associated with resistance to downy and powdery mildew in grapevine - Ricciardi, Valentina; Crespan, Manna; Maddalena, Giuliana; Migliaro, Daniele; Brancadoro, Lucio; Maghradze, David; Failla, Osvaldo; Toffolatti, Silvia Laura; De Lorenzis, Gabriella (Frontiers in Plant Science, 2024)
Among the main challenges in current viticulture, there is the increasing demand for sustainability in the protection from fungal diseases, such as downy mildew (DM) and powdery mildew (PM). Breeding disease-resistant grapevine varieties using resistance loci is a key strategy for better managing fungicide inputs. This study explores the diversity of grapevine germplasm (cultivated and wild) from Caucasus and neighbouring areas to identify genotypes resistant to DM and PM, based on 13 Simple Sequence Repeat SSR (SSRSimple Sequence Repeat) loci and phenotypical (artificial pathogen inoculation) analysis, and to identify loci associated with DM and PM resistance, via Genome-Wide Association Analysis GWAS (GWASGenome-Wide Association Analysis) on SNP Single Nucleotide Polymorphism (SNPSingle Nucleotide Polymorphism) profiles. SSR analysis revealed resistant alleles for 16 out of 88 genotypes. Phenotypic data identified seven DM and 31 PM resistant genotypes.GWAS identified two new loci associated with DM resistance, located on chromosome 15 and 16 (designated as Rpv36 and Rpv37), and two with PM resistance, located on chromosome 6 and 17 (designated as Ren14 and Ren15). The four novel loci identified genomic regions are rich in genes related to biotic stress response, such as genes involved in pathogen recognition, signal transduction and resistance response, emphasising the potential role of these loci in disease resistance. This study highlights potential candidate genes associated with resistance to DM and PM, providing valuable insights for breeding programs for resistant varieties. To optimise their utilisation, further functional characterization studies are recommended.